Шелеп - Перевощиков Генрих Ксенофонтович (Удмуртия, 2004)
Экземпляры: ф8 (20200722) / Инвентарный номер: 45482 / Цена: 149.00 / Сис.шифр: С(Удм) / Авт.знак: П 27 / ГРНТИ: 17.82.30 / ББК: 84(2Рос= Удм)